Jardín botánico, heterotopía y ciudad - Rodríguez Orte, Mariana (Universidad ORT Uruguay, 2018)
This essay explores the botanical garden as Michel Foucault’s definition of heterotopia, comparing it to the contemporary city and its phenomena. It seeks to expose the duality in which the existence of the botanical garden as artificial landscape masks its true artificial essence, and the city as a whole as heterotopy. For that purpose, the botanical garden is reflected upon as a reflected image of reality and as a yuxtaposed recreation of out of context and out of place realities. Both the contemporary city and the Botanical Garden are studied under the premise of Baudrillard;s hyperreality: contradictions and augmented realities blend, and questions about the preestablished and prepacked truth emerge.